The Role of QuizWhizzer in English Learning: A Descriptive Study to Increase the Learning Interest of 8th Grade Students - Muthoharoh, Siti; Sari, Dyah Ayu Nawang; Susanto, Sulistiyowati; Dewanti, Binar Ayu (Universitas Islam Lamongan, 2025)
This study aims to determine the extent to which the use of QuizWhizzer can increase student interest in learning. The method used in this research is descriptive quantitative. The research subjects were students of class VIII F and VIII G at SMPN 3 Lamongan totaling 60 students, but only 33 students were taken as samples in data collection in the form of student learning interest questionnaires. Indicators of student interest in learning questionnaires include attention, interest, feelings of pleasure, student involvement. The percentage results obtained for the student attention indicator are 60.24%, the student interest indicator is 64.36%, the feeling of pleasure indicator is 65.57%, the involvement indicator is 63.63%. The total of the four indicators is 63.45% and is in the High category. This study makes an important contribution in the development of technology-based learning methods by confirming the effectiveness of using QuizWhizzer application as an interactive learning media. The results show that QuizWhizzer not only significantly increases students' learning interest and motivation, but also strengthens students' active involvement in the learning process through interesting and fun interactive quizzes.